Outcome Measures for Evaluating Intimate Partner Violence Programs Within Clinical Settings: A Systematic Review of the Literature. (December 2017) - Sprague, Sheila; McKay, Paula; Madden, Kim; Scott, Taryn; Tikasz, Diana; Slobogean, Gerard P.; Bhandari, Mohit
Background: Multiple intimate partner violence (IPV) identification and assistance programs have been implemented across clinical settings. The results of these studies are inconclusive and frequently conflicting, resulting in clinical uncertainty and controversy regarding the merits of IPV identification and assistance programs. We aimed to describe the choice of outcome measures used in previously published randomized trials of IPV identification and assistance programs. Method: A comprehensive literature search was conducted in the Medline, Embase, PyscInfo, and CENTRAL databases. The outcomes assessed in each included study were extracted and categorized, and the methodological quality of each eligible study was assessed using the Cochrane Risk of Bias tool. Results: Of 20 eligible studies, 6 evaluated IPV identification programs and 14 studies examined IPV assistance programs. The included studies used 48 different outcomes that we classified into 10 categories. For identification studies, the most commonly used outcome categories were IPV disclosure (66.7%) and resource use (66.7%). The most commonly used outcome categories for the IPV assistance studies included IPV recurrence and severity (64.3%) and health outcomes (50%). The included studies demonstrated a number of methodological limitations as identified by the Cochrane Risk of Bias instrument. Conclusions: IPV identification and assistance programs are evaluated using many different outcome measures. Although this diversity enriches the IPV literature, it makes it challenging to compare studies. The results of this review highlight the challenges of conducting research in the field of IPV and the complexity of selecting, measuring, and interpreting outcomes.